Interplay between TRIM7 and antiviral immunity - Liu, Yiyang; Jiang, Lu; Sun, Xuemeng; Song, Yixuan; Liu, Yihan; Zhang, Leiliang (Frontiers in Cellular and Infection Microbiology, 2023)
TRIM7 has been demonstrated to have significant roles in promoting host defense against viral infections and regulating immune signaling pathways. As an E3 ubiquitin ligase, it catalyzes the ubiquitination of various substrates, including adaptor proteins (MAVS and STING) and transcription factors (NF-κB and IRF3), thereby exerting positive or negative regulation on immune signal pathways. However, viruses have developed immune evasion mechanisms to counteract TRIM7. Some viruses can inhibit TRIM7 function by targeting it for degradation or sequestering it away from its targets. Moreover, TRIM7 may even facilitate viral infection by ubiquitinating viral proteins, including envelope proteins that are critical for tissue and species tropism. A comprehensive understanding of the interaction between TRIM7 and antiviral immunity is crucial for the development of innovative treatments for viral diseases.